2002
DOI: 10.1081/ddc-120002843
|View full text |Cite
|
Sign up to set email alerts
|

Multi-unit Controlled Release Systems of Nifedipine and Nifedipine:Pluronic® F-68 Solid Dispersions: Characterization of Release Mechanisms

Abstract: Nifedipine (N) and nifedipine. Pluronic F-68 solid dispersion (SD) pellets were developed and characterizedfor drug release mechanisms from a multi-unit erosion matrix system for controlled release. Nifedipine was micronized using a jet mill. Solid dispersion with Pluronic F-68 was prepared by the fusion method. Nifedipine and SD were characterized by particle size analysis, solubility, differential scanning calorimetry (DSC), and x-ray diffraction (XRD) studies. Samples were subsequently processed into matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…15 Recently, poloxamers, a group of block copolymer nonionic surfactants, have attracted considerable attention for application in preparation of solid dispersions. [16][17][18] These polymers are widely used as emulsifiers, solubilizing agents, and suspension stabilizers in liquid, oral, topical, and parenteral dosage forms and also act as wetting agents and plasticizers, and have been reported for enhancing the solubility and bioavailability of sparingly soluble drugs in solid dosage forms. 19,20 Nine grades of poloxamers have been evaluated by Saettone and coworkers 21 as solubilizers for tropicamide, a poorly water-soluble drug.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, poloxamers, a group of block copolymer nonionic surfactants, have attracted considerable attention for application in preparation of solid dispersions. [16][17][18] These polymers are widely used as emulsifiers, solubilizing agents, and suspension stabilizers in liquid, oral, topical, and parenteral dosage forms and also act as wetting agents and plasticizers, and have been reported for enhancing the solubility and bioavailability of sparingly soluble drugs in solid dosage forms. 19,20 Nine grades of poloxamers have been evaluated by Saettone and coworkers 21 as solubilizers for tropicamide, a poorly water-soluble drug.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multiple mechanisms control the rate of drug release from the formulations. Mehta et al demonstrated that drug release systems governed by multiple mechanisms, such as diffusion and erosion, can exhibit pseudosteady state approaching zero-order release rates (44,46). A zero-order release is observed when the diffusion rate of the dissolution media into the matrix and the polymer dissolution rate are equal, resulting in a synchronized or constant drug-depleted layer (47).…”
Section: Discussionmentioning
confidence: 99%
“…[14] Recently, poloxamers, a group of block copolymer nonionic surfactants, have attracted considerable attention for application in preparation of SDs. [15][16][17] These polymers are widely used as emulsifiers, solubilizing agents, and suspension stabilizers in liquid, oral, topical, and parenteral dosage forms and also act as wetting agents and plasticizers, and have been reported for enhancing the solubility and bioavailability of sparingly soluble drugs in solid dosage forms. [18,19] Nine grades of poloxamers have been evaluated by Saettone et al [20] as solubilizers for tropicamide, a poorly water-soluble drug.…”
Section: Introductionmentioning
confidence: 99%